DNA lipid nanoparticles as alcohol-sensitive surrogates to trace microbial transmission and monitor hand hygiene - Lara Pfuderer; Hugo Sax; Robert Grass (Scientific Reports)
Abstract Understanding the transmission routes of microbial pathogens is essential for infection prevention and control in healthcare settings. However, using infectious microorganisms to this end is challenging and poses potential risks. We explored alcohol-sensitive DNA-encapsulating lipid nanoparticles (LNP) as surrogate tracers to investigate microbial transmission, including the effect of hand hygiene. LNPs embedded in various synthetic matrices were evaluated under controlled laboratory conditions to identify the optimal formulation. The chosen LNP glycerine and sucrose formulation was subsequently tested in patient care experiments, both with and without hand hygiene conducted according to established standards using alcohol-based hand rub (ABHR). Predefined contact surfaces and body sites were sampled and analysed for LNP integrity through quantitative polymerase chain reaction. The study revealed that the LNP formulation remained stable when dried on a surface. Hand hygiene using ABHR reduced LNP integrity to ≤ 1%. Without hand hygiene, LNPs transferred between surfaces maintained nearly 100% integrity. However, stability decreased during skin-to-skin transfer. In a typical patient care interaction, the study LNP formulation demonstrated a rapid, low-risk, and reliable approach for evaluating short pathogen transmission pathways, including the impact of hand hygiene. It shows promise as a diagnostic tool for assessing the effectiveness of transmission prevention measures in real-life clinical settings.